2013
DOI: 10.1149/2.011402jss
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reliable Polysilsesquioxane Passivation Layer fora-InGaZnO Thin-Film Transistors

Abstract: We report the fabrication of highly reliable amorphous InGaZnO (a-IGZO) passivated by a polysilsesquioxane-based passivation layer using a simple solution process. Results show that a copolymer of methylsilsesquioxane and phenylsilsesquioxane is an effective passivation layer. a-IGZO thin film transistors (TFT) passivated by this copolymer showed a small threshold voltage (V th ) shift of 0.1 V during positive bias stress, very small V th shift of less than 0.1 V during negative bias stress and a minimal V th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…We also observed that hump effect is less pronounced for both NBIS instability is largely caused by oxygen vacancies (V O ) [18]. We have recently reported that a high C and H concentration in the a-IGZO layer can contribute to the higher reliability especially during NBIS [15]. …”
Section: Bias Stress Reliabilitymentioning
confidence: 77%
See 2 more Smart Citations
“…We also observed that hump effect is less pronounced for both NBIS instability is largely caused by oxygen vacancies (V O ) [18]. We have recently reported that a high C and H concentration in the a-IGZO layer can contribute to the higher reliability especially during NBIS [15]. …”
Section: Bias Stress Reliabilitymentioning
confidence: 77%
“…More details about the polysilsesquioxane passivation layers used in this work is reported in Ref. [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower energy peak around 530 eV indicates the oxygen ion peak originating from the metal-oxygen bond (M-O), the peak around 531.5 eV indicates the oxygen deficient region (O def ), and the peak around 532.3 eV indicates a weak bond such as O-H (O weak ). [19][20][21][22] Figure 7 shows the plots of area ratio calculated from the curve-fitted O1s peaks, and shows the slight but definite decrease in O def and increase in M-O with increasing annealing temperature.…”
Section: Degrading Factor Of Tfts In High Laser Energymentioning
confidence: 99%
“…The developed ADC consists of an inverter-based comparator and an encoder with n-channel a-IGZO TFTs. The TFTs have a bottom gate structure with a methyl-siloxane-based organic spin-on-glass (SOG) passivation layer, which reduces the plasma damage on the active layer [19]. After examining comparators and logic gates with a-IGZO TFTs, a three-bit ADC was developed.…”
Section: Introductionmentioning
confidence: 99%